2017
DOI: 10.1108/ijsms-05-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

The distant fan segment

Abstract: Purpose With the available technological tools, fans are able to access sport products regardless of geographic proximity. Through technology, fans can follow sports teams from other countries. In contrast to previous research focused on the local fan, in this paper we report on a study of a group of distant fans – Chinese National Basketball Association (NBA) fans – as the focal object. The study was guided by three questions: RQ1: what motives drive a distant fan’s involvement with their favorite NBA team? R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…television) and even other social media platforms (e.g. YouTube, Facebook, Snapchat, and Twitch) (Behrens & Uhrich, 2019;Kerr & Gladden, 2008;Maderer et al, 2016;Pu & James, 2017). It should be noted that satellite fans are different from displaced fans, which refer to local fans who moved away from their hometown, yet still support the hometown team (Collins et al, 2016; Pu & James, 2017).…”
Section: Satellite Fansmentioning
confidence: 99%
See 3 more Smart Citations
“…television) and even other social media platforms (e.g. YouTube, Facebook, Snapchat, and Twitch) (Behrens & Uhrich, 2019;Kerr & Gladden, 2008;Maderer et al, 2016;Pu & James, 2017). It should be noted that satellite fans are different from displaced fans, which refer to local fans who moved away from their hometown, yet still support the hometown team (Collins et al, 2016; Pu & James, 2017).…”
Section: Satellite Fansmentioning
confidence: 99%
“…Satellite fans have been considered as a unique focal object in sport fandom research. For example, studies found that satellite fans support the sport teams for several different reasons, such as media coverage, style of play, presence of star player(s), or team history (Kerr & Emery, 2011;Kerr & Gladden, 2008;Pu & James, 2017). In addition, satellite fans may have a unique formation process of psychological attachment with the teams due to the geographical distance (Kerr & Emery, 2011;Pu & James, 2017).…”
Section: Satellite Fansmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting a distant football team was uncommon at that time. Technical development made it possible to watch a game through television broadcast or on the internet, offering a chance for people to focus on a team away from home and even become a fan of the distant team (Pu & James, 2017). Compared with the identification on the local team, individual's identification on a non-local team is less related to the community and lack of geographical proximity, which implicates its intangibility and the difference in antecedent and maintenance (Kerr & Emery, 2011;Wann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%